PELATIHAN SISTEM AKUNTANSI PENGELOLAAN LAPORAN KAS IPNU IPPNU DESA KWAYANGAN KECAMATAN KEDUNGWUNI KABUPATEN PEKALONGAN - Izaty, Santi Nailul; Febriani, Fenti; Kurniawan, Pratomo Cahyo (Sekolah Tinggi Ilmu Ekonomi AMA, 2024)
The most important part of financial management is cash management. Cash is one of the most liquid financial assets because it is used for the company's operational activities such as paying the company's obligations. Holding this Community Service aims to provide training to the non-profit institution IPNU IPPNU Kwayangan Village on the basics of accounting and making financial statements, as well as managing cash statements properly and correctly. With this training, it is hoped that IPNU IPPNU Kwayangan Village members, especially cash managers, can better understand making financial statements and cash management due to this service. The method used in this service is delivering material directly to the IPNU IPPNU management of Kwayangan Village. The material we bring about making structured records according to accounting rules can be easily understood. As well as guiding the management and participants of IPNU IPPNU until it can succeed in its implementation. The result of the dedication obtained by the participants was an increase in knowledge and adequate insight into cash management. In providing guidance, it is carried out optimally, and structured to separate cash receipt journals and cash expenditure journals neatly and professionally.